PROPERTIES OF NORMAL STRENGTH CONCRETE WITH TREATED CRUSHED BRICK AND RECYCLED CONCRETE AS COARSE AGGREGATE - Ayada, Marwa; Tariq Al-Shafi’i, Nagham (Journal of Engineering and Sustainable Development, 2022)
The results of a research program conducted at the University of Mustansiriayah in Iraq to analyze the qualities of concrete created with crushed bricks and crush concrete are presented in this paper. To make a suitable aggregate, these materials were crushed. Some aggregates were treated, while others were not. The properties investigated were the workability and the density of fresh the aggregates of crushed bricks and crush concrete were treated in some mixtures and others were not treated. The properties investigated were the workability and the density of fresh concrete, and the compressive strength and tensile splitting strength behavior of hardened concrete. Different replacement ratios (0, 50%, and 100%) were investigated. The concrete rustles produced with recycled aggregates were compared with a reference concrete produced with natural coarse aggregates currently used in Iraq. Using surface treatment with silicate solution, when comparison to RCA50 and RCA100 samples, TRCA50 and TRCA100 compressive strength improved by roughly 5.05 percent and 5.9 percent after 28 days, respectively. And came closer to concrete with natural aggregate R, and improved 3.25% and 4.6% in TBR100 and TBR50, respectively compared. With the BR100 and BR50 respectively, they added a cross resistance of R for TRAC100% when silica fume was added, approaching R at TBR100%. Aggregates indicate that this type of concrete can be used in various precast applications.